ETHICS AND COVID-19:: FROM HEALTH RECOMMENDATIONS TO MORAL DUTIES - Delaide da Silva, Thiago (Sofia, 2023)
This essay aims to investigate whether we have a moral obligation to follow health recommendations in the context of the COVID-19 pandemic. To this end, I try to raise this discussion from Kantian deontology, utilitarianism and ethics based on rights, asking whether the health recommendations related to the pandemic should be generically interpreted as moral duties. The text also discusses some possible objections to taking health recommendations as moral duties and seeks to reflect about how we can respond to them. The text concludes by defending that, through the moral theories presented, there are reasons to sustain that we have a moral duty to follow the health recommendations in the face of the COVID-19 pandemic scenario.
Keywords: ethic; pandemic; COVID-19; health recommendations; moral duties